PERMAINAN TRADISIONAL 3 JADI TERHADAP PROGRESIFITAS DEMENSIA PADA LANSIA DI KABUPATEN MOJOKERTO - Nova Farkhatus Solikhah; Joni Haryanto; Andri Setiya Wahyudi (Fakultas Ilmu Kesehatan, 2016)
Elderly at risk of dementia is caused by a decline in cognitive function. Dementia is also followed by depression syndrome. Intervention traditional game 3 jadi used to train cognitive function and reduces depression of elderly. The traditional game 3 jadi is one form of transmissive reminiscence therapy that use the culture has been known by the people of Dusun Kedungsumur. The study aim to analyze effect of the traditional game 3 jadi against the progression of dementia in the elderly.Design of research was quasy experimental study. The target population were 15.341 respondents in Kabupaten Mojokerto. The independent variable was the traditional game 3 jadi. The dependent variable was cognitive and depression level. Data was collected using ECAQ (Elderly Cognitive Assessment Questionnaire) and GDS (Geriatric Depression Scale). The statistical analysis used were Independent T-Test and Paired T-Test with a significance level of α ≤ 0.05.Statistical test results Paired T-Test for cognitive was p = 0.010 and depression was p = 0.000. Statistical test results Independent T-Test for cognitive was p = 0.003 and depression was p = 0.000 so that the results showed that there were significant traditional game 3 jadi against the progression of dementia.It can be concluded that the effect of the traditional game 3 jadi against the progression of dementia is very strong. Elderly will be get increased cognitive level and decline depression level to satisfy their need for self care after finished their game.